Drivers of Plankton Distribution Across Mesoscale Eddies at Submesoscale Range - Hernández-Hernández, Nauzet; Arístegui, Javier; Montero, María F.; Velasco-Senovilla, Esther; Baltar, Federico; Marrero-Díaz, Ángeles; Martínez-Marrero, Antonio; Rodríguez-Santana, Ángel (Frontiers in Marine Science, 2020)
Cyclonic and anticyclonic eddies are common mesoscale features in the flow past the Canary Islands throughout the year. While drifting southwards, eddy pairs interact among them but also with upwelling filaments and eddies generated at the coastal jet of the nearby African upwelling system. These interactions force the generation of frontal zones where ageostrophic secondary circulation (ASC) may occur. With the aim of contributing to understand how meso-submesoscale interactions modulate plankton distribution, we carried out an interdisciplinary cruise across a mesoscale eddy field. The sampled region was characterized by the presence of a cyclonic eddy interacting with two anticyclonic eddies and an upwelling filament. High resolution sampling allowed us to assess the upwelling/downwelling processes associated with eddy pumping and ASC, the injection of nutrients into the euphotic zone, and the subduction of particles related to these processes. The planktonic community, which included heterotrophic bacteria, cyanobacteria-like Prochlorococcus and Synechococcus, pico and nanoautotrophic eukaryotes and heterotrophic nanoflagellates, showed a heterogeneous distribution in response to meso-submesoscale processes. Redundancy Analysis and plankton distribution suggest that while the distribution of small organisms (picoplankton) is modulated by a combination of physical and biogeochemical drivers, the distribution of larger autotrophic and heterotrophic nanoflagellates is modulated by nutrient inputs and grazing, respectively. These observational results provide new insights in the study of the impact of mesoscale structures in the dynamics of nutrients, chlorophyll and planktonic communities, valuable to validate theoretical and modeling studies.